Pengolahan Limbah Cair Industri Migas dengan Adsorpsi Pada Kolom Fixed – Bed - Kartika Udyani; Cahyadi Marta Pamungkas; Ticha Maharani (Seminar Nasional Teknik Kimia Kejuangan, 2017)
Petroleum processing industry activities generate wastewater containing phenol. If the effluent directly released into the environment will cause environmental pollution. This study aims to determine the effect of flow rate and height of bed to the reduction in the phenol content in wastewater oil and gas industry by using activated carbon adsorbent in a fixed-bed column. The study begins with the pre-treatment of wastewater by aeration to separate the oil content in the waste water. Furthermore sewage flowed into a fixed-bed column at various flow rates and high bed. Effluent from each - each variation of measured and calculated% concentration phenol removal. The results showed that the reduction in flow rate increases the amount of phenol is absorbed. For the high bed 25%, 50% and 75% of the fixed-bed column height, the higher the bed the higher the amount of phenol is absorbed. Best results are obtained on a high bed 75% and a flow rate of 0.8 mL / sec with% phenol removal amounted to 98.99%